The results of investigating the efficacy and safety of non-medical switching from the original rituximab to its biosimilar in rheumatoid arthritis patients (AMBIRA study) - M. A. Korolev; Yu. B. Ubshaeva; N. Y. Banshchikova; E. A. Letyagina; A. A. Mullagaliev (Научно-практическая ревматология, 2021)
Wide usage of biologic disease-modifying anti-rheumatic drugs (DMARDs) biosimilars in clinical practice has greatly increased the availability of biologic therapy for rheumatic patients. Nevertheless, not only economic expediency but efficacy and safety are the key principals of any treatment including biologic DMARDs.Objective. To investigate the efficacy and safety of switching from the original rituximab (MabThera®, “F. Hoffmann-La Roche Ltd.”, Switzerland) to its biosimilar (Acellbia®, “BIOCAD”, Russia) by non-medical reasons in rheumatoid arthritis patients.Subjects and methods. 40 rheumatoid arthritis patients on basic therapy who had taken at least one course of original rituximab (MabThera®) 1000 mg twice in 2 weeks more than 6 months ago were included. They were switched to equal-dose biosimilar (Acellbia®) by non-medical reasons and were observed throughout the year. At 12, 24 weeks and one year after switching dynamics of the next parameters were evaluated: pain level according to visual analogue scale (VAS), tender joint count (TJC), swollen joint count (SJC), acute inflammatory and immunological markers, disease activity score (DAS28) calculated using erythrocyte sedimentation rate (DAS28-ESR) or C-reactive protein (DAS28-CRP), health assessment questionnaire (HAQ) index and safety profile.Results. All the data are presented as median of indicator in the moment of measurement after switching therapy (Meperiod). In 12-week period TJC [(Me]_0=9.50, Me_12=6.0, p< 0.01) and SJC (Me_0=2,0, Me_12=1,0, p<0.01) were decreased with positive dynamics on the 24 and 48 weeks. Also, similar results were observed in the VAS pain level. DAS28 showed significant decreasing during observation: Me0=4.38, Me24=3.55, Meyear=3.49, p<0.01 for DAS28-ESR; and Me0=3.91, Me24=3.15, Meyear=3.03, p<0.01 for DAS28-CRP. Immunological markers were increased or stable during the first months after switching, but then they were significantly decreased: Me0=45.0 U/ml, Meyear=23.0 U/ml, p<0.01 for rheumatoid factor; and Me0=88.0 U/ml, Meyear=50.5 U/ml, p<0.01 for anti-cyclic citrullinated peptide. HAQ index was stabilized during 1 year: Me0=1.00, Meyear=0.75, p<0.01. Severe infusion reactions on Acellbia® were not observed, safety profile was similar to MabThera®.Conclusion. Our investigation revealed that non-medical switching from original rituximab (MabThera®, “F. Hoffmann-La Roche Ltd.”, Switzerland) to its biosimilar (Acellbia®, “BIOCAD”, Russia) has no significant influence on the therapy efficacy and safety.